Penjangkauan Pekerja Seks Perempuan (Psp) Sebagai Upaya Pencegahan dan Penanggulangan HIV dan AIDS (Studi Kasus di LSM Sokoguru): Outreach to Women Sex Workers (PSP) as an Effort for the Prevention and Control of HIV and Aids (Case Study at the NGO Sokoguru) - Karisma Indah Lestari; Sigit Ambar Widyawati; M. Yusuf (Journal of Holistics and Health Sciences (JHHS), 2022)
In efforts to control HIV transmission, it is very important to achieve outreach targets. In the female sex worker population in Indonesia, there is a need for alternative HIV testing to increase the number of female sex worker who know their status. Sokoguru Fondation is one of the implementing units for the Global Fund New Funding Model project for HIV & AIDS prevention and control. Sokoguru Fondation is one of the sub-recipients and the Kalandara Foundation for the Global Fund project through PR (principal recipient) and IAC (Indonesia AIDS Coalition) for HIV/AIDS prevention and control efforts in key populations in the districts of Semarang, Pati, Grobogan, Rembang, and Blora. The first quarter outreach achievements at Sokoguru Foundation in February, March, and April were 55.6%, 95.4%, and 77%. This achievement has not yet reached the outreach target of 304 Female Sex Workers. In the first quarter HIV test results at the Sokoguru Foundation in February, March, and April were 14.5%, 28.4% and 4.7%. This achievement has not yet reached the outreach target of 359. In 2022, PSP outreach reached 5, namely in February 4 and April 1 person was detected with HIV+ and is still being sought for follow-up assistance. ABSTRAKDalam upaya penanggulangan penularan HIV, sangat penting untuk mencapai target penjangkauan. Pada populasi pekerja seks perempuan (PSP) di Indonesia, ada kebutuhan alternatif tes HIV untuk meningkatkan jumlah PSP yang mengetahui statusnya. LSM Sokoguru merupakan salah satu implementing unit untuk proyek Global Fund New Funding Model untuk upaya pencegahan dan penanggulangan HIV & AIDS. Lembaga Swadaya Masyarakat (LSM) Sokoguru merupakan salah satu sub-sub recipient dan Yayasan Kalandara untuk proyek Global Fund melalui PR (principal recipient) dan IAC (Indonesia Aids Coalition) untuk upaya pencegahan dan penanggulangan HIV/AIDS pada populasi kunci di wilayah Kabupaten Semarang, Pati, Grobogan, Rembang, dan Blora. Capaian penjangkauan kuartal 1 di Yayasan Sokoguru pada bulan Februari, Maret, dan April sejumlah 55,6%, 95,4%, dan 77%. Capaian tersebut belum mencapai target penjangkauan yaitu sejumlah 304 PSP. Pada capaian test HIV kuartal 1 di Yayasan Sokoguru pada bulan Februari, Maret, dan April sejumlah 14,5%, 28,4% dan 4,7%. Capaian tersebut belum mencapai target penjangkauan yaitu sejumlah 359. Pada tahun 2022, penjangkauan PSP didapatkan 5, yaitu pada bulan februari 4 dan April 1 orang yang terdeteksi HIV+ dan masih diupayakan untuk tindak lanjut pendampingan.